Introduzione alla meccanica statistica Un approccio assiomatico elementare - Narducci, Dario (UNICApress, 2020)
The teaching of science subjects in Italian universities has undergone profound changes with the introduction of the 1999 reform of the autonomy of universities and the consequent introduction of course credits, which has forced degree programs to significantly reduce the number of lecture hours that can be delivered. This has induced if not forced many professors to simplify content, heavily reducing the exemplifications that can be offered and also, often, foregoing the deductive rigor that many disciplines might require. This text is the result of an attempt to present the fundamentals of statistical mechanics to Italian master's degree students by employing an axiomatic approach. The reader is guided through a theory-building process that helps him or her understand its main conceptual junctures, stimulating interest and critical thinking. Shying away from formalism, the volume is intended as a compromise between the need to keep the teaching load proportionate to the hours of classes given and the mathematical skills of the students, while at the same time ensuring sufficient examples of applications of the theory to appreciate its relevance and predictive potential.